The relationship between students' self-esteem level and anxiety level in completing theses during the COVID-19 pandemic - Fitri, Amira Melati; Maulana, Muhammad Ali; Fradianto, Ikbal (Universitas Tanjungpura, 2024)
Background: The Covid-19 pandemic significantly disrupted educational systems, including higher education, where students faced challenges in completing theses due to remote learning, limited access to resources, and increased anxiety. Self-esteem plays a crucial role in shaping students